Exploring the experiences and perceptions of coaches, athletes, and integrated support teams towards the management of three national Paralympic teams - Alexander, D.; Bloom, G. A.; Bentzen, M.; Kenttä, G. (Psychology of Sport and Exercise, 2023)
Highlights • Multiple sources of data collected from head coaches, athletes, and support teams. • Head coaches managed a diverse team of athletes regarding age, finances, and disability. • Head coaches used their support team to maintain cohesion and well-being in the team. • First step in conducting and promoting international parasport coaching research.